Innovative Mobile Application UI/UX for Gestari Waste Bank Administration Using Activity-Centered Design - Charisma, Dhea Intan; Agusdin, Riza Prapascatama (Journal of Applied Informatics and Computing, 2025)
Bank Sampah Gestari, located in Dusun Gesikan, Panggungharjo, Sewon, Bantul, runs a routine household waste sorting program every “Minggu Legi.” In its operation, administrative officers still rely on manual data recording using notes and books, leading to data accumulation and inefficient recap processes, especially with the growing number of customers. The absence of a digital system to support the recording process presents a major challenge in achieving optimal administration. This study aims to design the User Interface (UI) and User Experience (UX) of a mobile-based administrative system for Bank Sampah Gestari using the Activity Centered Design approach. The approach focuses on the core activities performed by users during administrative tasks. The design process was informed by observations and interviews with administrative staff and was used to develop application flows and interfaces aligned with user needs and the bank’s business processes. The prototype was evaluated through two usability testing iterations, measuring five usability aspects: learnability, efficiency, memorability, errors, and satisfaction. Results showed notable improvements in all aspects. Learnability increased from 78% to 94%, efficiency from 0.0155 to 0.0440 goals/sec, memorability from 2.75 to 3.85, error rate decreased from 0.44 to 0.12, and satisfaction rose from 25.5 to 84.5. In conclusion, the proposed interface design significantly enhances ease of use, operational efficiency, and user satisfaction. The design can serve as a recommendation for developing a more structured, effective, and user-friendly digital administrative system for Bank Sampah Gestari.